Business Model Analysis to Strengthen the Competitiveness in Construction Services SME - Handoko, Irfan; Effendi, Rusfian; Kurniawan, Cristophorus; Deny, Muhammad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study attempts to map the business models of construction service SMEs to recommend new business model formulations that are relevant to the company's needs and challenges. This research maps the existing business models of companies, then analyzes their environmental conditions so that relevant strategies can be recommended and are expected to contribute to business development. This research was conducted using descriptive analysis, mapping the company's business model using the Business Model Canvas (BMC) approach and a SWOT analysis. A cross-analysis used to formulate a new business model. The study results show that companies need to offer value propositions that are difficult for competitors to replicate, rather than relying solely on low prices. Furthermore, companies are also required to leverage online promotions to reach a wider customer segment. Internal training and certification can be implemented to enhance service delivery and implement continuous improvement across the company. The company's customer base is still relatively young, so additional promotional efforts are needed to expand its market segment, including through social media. The new business model suggests the company should further improve the quality of its work through internal training, certification, and collaboration with relevant parties. This research offers new insights into the business models of construction service companies to develop and strengthen their presence in the industry. It is hoped that the formulation of this business model will provide stakeholders with diverse perspectives for policymaking and contribute to a more comprehensive literature.